PENGARUH WAKTU EKSTRAKSI TERHADAP TOTAL FENOLAT DAN NILAI IC50 DARI EKSTRAKSI KULIT BUAH NAGA MERAH (Hylocereus polyrhizus) - Amalia Noviyanty; Chitra Anggriani Salingkat; Syamsiar (Jurnal Pengolahan Pangan, 2019)
The skin of the red dragon fruit is a waste that is still very rarely used. While the percentage of red dragon fruit skin is 30% to 35% of the weight of the fruit. Dragon fruit peels still contain quite high antioxidant compounds, antioxidant compounds can fight oxidation in the body. Utilization is done on the skin of dragon fruit, one of which is to extract it so that it can be used as a basis for a variety of functional foods that will benefit health. The study aims to determine the effect of extraction time on total phenolics and antioxidant activity (IC50 values) on red dragon fruit peel extracts and also obtain the optimum extraction time to get the highest or best total phenol and IC50 values. Extraction time used consists of 3 levels, namely 24 hours (1 day), 48 hours (2 days) and 72 hours (3 days). The data obtained were analyzed using the Completely Randomized Design which was applied to the observation of total phenolics and IC50 values, if the treatment had a very significant or real effect followed by continued BNJ testing at 1% or 5% level. The results showed that the extraction time had a very significant effect on the total phenolics and IC50 values ​​of dragon fruit peel extract and the extraction time of 3 hours gave the highest or best total phenolics and IC50 values ​​of 78.78 ppm and 115.90 ppm.